Metal-modified MXene nanosheet three-dimensional composite material as well as preparation method and application thereof

By introducing Cu2+ and K3[Fe(CN)6] on the surface of MXene nanosheets, the PMX composite material is formed, which solves the problem of limited adsorption performance of existing adsorbents in high acidity and high salinity environments, and achieves efficient and stable adsorption of cesium ion, which is suitable for nuclear wastewater treatment and rare metal resource recovery.

CN119549105APending Publication Date: 2025-03-04SUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411751977.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The adsorption properties of existing adsorbents in high acidity and high salinity environments are limited, their stability is insufficient, and their preparation process is complex, which limits their application in industrial production.

Method used

By introducing Cu2+ and K3[Fe(CN)6] in situ on the surface of MXene nanosheets, a metal-modified MXene nanosheet three-dimensional composite material (PMX) is formed, and it is functionalized on the surface of MXene using Cu-PBA to achieve efficient adsorption of cesium ions.

Benefits of technology

PMX exhibits fast, efficient and selective cesium ion adsorption capability in acidic and high saline water environments, with adsorption capacity up to 408.2 mg/g and maintains stable performance during multiple adsorption-regeneration cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549105A_ABST
    Figure CN119549105A_ABST
Patent Text Reader

Abstract

The invention provides a metal-modified MXene nanosheet three-dimensional composite material as well as a preparation method and application thereof, and belongs to the technical field of environmental governance and resource recovery. The composite material has a stable three-dimensional structure, an MXene suspension and a copper source solution are mixed, Cu < 2 + > is fixed through ultrasonic action, then a [Fe (CN) 6] < 3-> solution is introduced for chemical reaction, and the uniformly-loaded PBA-MXene composite material (PMX) is formed. The obtained material shows rapid, efficient and selective adsorption capacity on cesium ions (Cs < + >) in an acidic and high-salt water body environment, the adsorption capacity reaches up to 408.2 mg / g, and the performance can be kept stable in multiple adsorption-regeneration cycles. The method is suitable for radioactive wastewater treatment and rare metal resource recovery, and especially has an important application value in strongly acidic and complex environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmental management and resource recovery, and specifically relates to a metal-modified MXene nanosheet three-dimensional composite material (hereinafter referred to as PMX) and its preparation method and application, especially in the field of cesium ion (Cs + ) Application in selective enrichment. Background Art

[0002] Cesium ion (Cs + ), especially its radioactive isotopes 137 Cs is one of the main pollutants in nuclear waste. Due to its long half-life of 30.17 years and its high solubility and mobility, cesium ions pose a serious threat to the environment and human health. At the same time, as a rare alkali metal, cesium has important application value in the high-tech field due to its unique chemical properties and atomic structure, and is a key element in the strategic resource planning of many countries.

[0003] Currently, the main methods for removing and recovering cesium ions include precipitation, membrane separation, ion exchange and adsorption. Among them, adsorption technology has become the main means of treating cesium-containing wastewater due to its high efficiency, simple operation and low energy consumption. However, although existing adsorbents (such as Prussian blue and its analogs) have good selectivity, their microcrystalline structure limits their adsorption performance in highly acidic and high salinity environments, and their adsorption capacity is low (usually no more than 160 mg / g). In addition, its insufficient stability in complex environments (such as high-salinity water bodies) has hindered the further promotion of its practical application.

[0004] The existing technology uses a top-down method to peel off the granular Prussian blue MOF material into a two-dimensional layer-like Prussian blue MOF material, which significantly improves the adsorption rate and adsorption amount. However, the preparation method is complicated and has limitations for industrial production. Therefore, how to utilize the unique properties of the adsorbent while enhancing its chemical stability has become the key to research. Summary of the invention

[0005] In order to solve the problems of poor stability and complex preparation of existing adsorbents, the present invention uses MXene suspension to introduce Cu 2+ and K3[Fe(CN)6] to form a 3D composite material PMX. Cu-PBA was functionalized on the MXene surface by in situ synthesis to form a PMX composite material. The synergistic effect of the two was used to achieve efficient adsorption, which can selectively adsorb cesium ions (Cs + ), especially in complex environments (acidic conditions and seawater), providing new methods for nuclear wastewater treatment and resource recovery.

[0006] The present invention adopts the following technical scheme.

[0007] A metal-modified MXene nanosheet three-dimensional composite material comprises a MXene nanosheet and a metal complex on its surface, wherein the metal complex comprises K2Cu3(Fe(CN)6)2.

[0008] The present invention discloses a method for preparing the above-mentioned metal-modified MXene nanosheet three-dimensional composite material, comprising the following steps: reacting copper salt and K3[Fe(CN)6] on MXene nanosheets to prepare the metal-modified MXene nanosheet three-dimensional composite material.

[0009] Preferably, the method for preparing the above-mentioned metal-modified MXene nanosheet three-dimensional composite material comprises the following steps: mixing copper salt and MXene nanosheets, and then mixing with K3[Fe(CN)6] to prepare the metal-modified MXene nanosheet three-dimensional composite material.

[0010] Furthermore, the method for preparing the above-mentioned metal-modified MXene nanosheet three-dimensional composite material includes the following steps: mixing copper salt and MXene nanosheets in a solution, and then mixing with K3[Fe(CN)6] to prepare the metal-modified MXene nanosheet three-dimensional composite material.

[0011] Furthermore, the method for preparing the above-mentioned metal-modified MXene nanosheet three-dimensional composite material includes the following steps: mixing a copper salt solution and a MXene nanosheet solution, and then mixing them with K3[Fe(CN)6] to prepare a metal-modified MXene nanosheet three-dimensional composite material.

[0012] Furthermore, the method for preparing the above-mentioned metal-modified MXene nanosheet three-dimensional composite material includes the following steps: mixing a copper salt solution and a MXene nanosheet solution, centrifuging the mixture, and then mixing the precipitate with a K3[Fe(CN)6] solution to prepare a metal-modified MXene nanosheet three-dimensional composite material.

[0013] In the present invention, centrifugal treatment and mixing treatment are conventional techniques, such as using ultrasound for mixing treatment. Preferably, the mixing treatment time is 5 to 50 hours, preferably 10 to 40 hours, and more preferably 20 to 30 hours.

[0014] In the present invention, MXene nanosheets are prepared from Ti3AlC2. The specific preparation operation is conventional technology, and the MXene nanosheets can be prepared by exfoliating Ti3AlC2 using a hydrochloric acid / lithium system.

[0015] In the present invention, the copper salt is one or more of water-soluble copper salts and alcohol-soluble copper salts, such as one or more of copper nitrate, copper chloride, copper sulfate and copper acetate.

[0016] In the present invention, the solvent in the solution includes water and alcohol, wherein the alcohol includes small molecule alcohol. As common sense, the solvents corresponding to different solutes can be the same or different.

[0017] The invention discloses a three-dimensional adsorbent, the active component of which includes the above-mentioned metal-modified MXene nanosheet three-dimensional composite material.

[0018] The present invention discloses a method for preparing the above-mentioned three-dimensional adsorbent, comprising the following steps: reacting copper salt and K3[Fe(CN)6] on MXene nanosheets, and then drying the reaction product to obtain the three-dimensional adsorbent.

[0019] The present invention discloses the use of the above-mentioned metal-modified MXene nanosheet three-dimensional composite material or three-dimensional adsorbent as or in the preparation of an adsorption material.

[0020] Furthermore, the present invention discloses the use of the above-mentioned metal-modified MXene nanosheet three-dimensional composite material or three-dimensional adsorbent as or in the preparation of metal adsorption materials.

[0021] Furthermore, the present invention discloses the use of the above-mentioned metal-modified MXene nanosheet three-dimensional composite material or three-dimensional adsorbent as or in the preparation of radioactive metal adsorption materials.

[0022] In the present invention, the radioactive metal includes cesium, such as cesium ions (Cs + ), especially its radioactive isotopes 137 As an example, the adsorbent material of the present invention exhibits excellent performance in nuclear wastewater treatment and radioactive cesium ion enrichment, especially rapid adsorption (reaching equilibrium within 5 minutes) and high adsorption capacity (408.2 mg / g).

[0023] The present invention discloses a method for adsorbing metals, comprising the following steps: mixing the above-mentioned metal-modified MXene nanosheet three-dimensional composite material or three-dimensional adsorbent with a system containing metal to complete the adsorption of the metal.

[0024] Preferably, the system containing the metal is a solution; the metal is a radioactive metal, such as cesium ions (Cs + ), especially its radioactive isotopes 137 Cs.

[0025] The present invention provides a metal-modified MXene composite material and a preparation method and application thereof, which belongs to the technical field of environmental management and resource recovery. The composite material is prepared by in-situ introduction of Cu on the surface of MXene nanosheets. 2+ The MXene suspension was mixed with the copper source solution and the Cu was fixed by ultrasound.2+ , and then introduce [Fe(CN)6] 3- The solution undergoes chemical reactions to form a uniformly loaded PBA-MXene composite material (PMX). The resulting material is highly resistant to cesium ions (Cs + ) exhibits rapid, efficient and selective adsorption, with an adsorption capacity of up to 408.2 mg / g, and can maintain stable performance in multiple adsorption-regeneration cycles. Its adsorption mechanism mainly includes the synergistic effect of ion exchange and electrostatic attraction. The present invention is suitable for the treatment of radioactive wastewater and the recovery of rare metal resources, especially in strong acidic and complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The figure is a flow chart of the preparation of PMX.

[0027] Figure 2 For morphology characterization, (ac) SEM (df) TEM images of Cu-PBA, MXene, and PMX, and (g) EDS mapping of C, N, K, Fe, Cu, and Ti.

[0028] Figure 3 Composition analysis, including (a) XRD of Cu-PBA, MXene and PMX, (b) FT-IR of Cu-PBA, MXene and PMX, (c) XPS spectrum of PMX; (d) C 1s XPS spectrum of PMX.

[0029] Figure 4 Fitting curves of the adsorption kinetics of Cu-PBA, MXene, and PMX on Cs+ (pH = 1, m / V = 1 g / L, C0 = 100 mg / L and T = 298.15 K).

[0030] Figure 5 is the adsorption isotherm at different temperatures, nonlinear isotherm model (pH = 1, initial Cs + The concentration range is 0.1 to 1500 mg / L, m / V=1 g / L).

[0031] Figure 6 The adsorption selectivity and the influence of water environment are shown in Figure 2, where (a) the adsorption of different metal ions by PMX in HNO3 solutions with different concentrations, and (b) the Cs adsorption of PMX in different solutions. + Removal efficiency.

[0032] Figure 7 The cycling performance of PMX.

[0033] Figure 8 The PMX with different Cu-PBA loadings on Cs in 5 h + adsorption effect.

[0034] Fig. 9 Figure 2 shows the effect of PMX with different metal-PBA loadings on Cs in 5 h. + adsorption effect. DETAILED DESCRIPTION

[0035] The present invention mixes copper salt and MXene nanosheets, and then mixes them with K3[Fe(CN)6] to prepare a metal-modified MXene nanosheet three-dimensional composite material. The adsorbent material exhibits excellent performance in nuclear wastewater treatment and radioactive cesium ion enrichment, especially rapid adsorption (reaching equilibrium within 5 minutes) and high adsorption capacity (408.2 mg / g).

[0036] The preparation method includes: first, preparing MXene nanosheets, etching MAX in a mixed solution of HCl and LiF for 24 hours, then centrifuging and ultrasonically treating, and finally obtaining a uniformly dispersed MXene suspension. Then, the MXene suspension is mixed with a copper source solution, and the Cu is fixed by ultrasonic action. 2+ , and then introduce [Fe(CN)6] 3- The solution undergoes chemical reaction to form a uniformly loaded PBA-MXene composite (PMX).

[0037] The following experiments illustrate the technical progress of the present invention. The raw materials involved are conventional products, and the specific preparation operations and performance tests are all conventional technologies. The salts used in the preparation of the solution are metal nitrates or chlorides, such as CsCl. 0.5 M NaOH and HCl are prepared to control Cs + The pH of the solution.

[0038] Synthesis Example Preparation of MXene Nanosheets 1g Ti3AlC2 (MAX) powder was added to a mixed solution containing 20 mL HCl (9 mol / L) and 1.5g Li and etched at 45°C for 24 h. Then, the obtained suspension was first centrifuged and washed with 9 mol / L HCl, then washed with deionized water and centrifuged until the pH value of the solution reached 6.5. The precipitate was collected and dispersed in water, and the suspension was ultrasonically treated for 1h under nitrogen environment. The ultrasonic suspension was centrifuged at 4500 rpm for 5min. Finally, the upper layer of liquid was retained to obtain a uniformly dispersed Ti3C2 MXene dispersion, and the concentration c=25 mg / mL was determined.

[0039] Example 1 Preparation of PMX adsorption material See also Figure 1 To prepare the composite material, 4 mL of the above MXene suspension was diluted to 50 mL. Subsequently, 6 mmol of copper nitrate was dissolved in 50 mL of ethanol solution and added to the MXene suspension, and the precipitate was separated by centrifugation after conventional dispersion; the precipitate was redispersed in 50 mL of ethanol solution, and 50 mL of K3[Fe(CN)6] (6 mmol) ethanol solution was added to the above dispersion; the mixture was ultrasonically treated and then stirred for 24 h; the material was washed by repeated centrifugation with ultrapure water and ethanol, and washed after freeze drying, and the obtained material was called PMX.

[0040] The morphologies of Cu-PBA, MXene and PMX are as follows: Figure 2 As shown, Cu-PBA nanoparticles were successfully prepared. The prepared Cu-PBA has an irregular shape structure and is prone to agglomeration. Figure 2 (a, d); Single or few-layer MXene nanosheets were successfully prepared by etching method Figure 2 (b, e); By 2+ and K3[Fe(CN)6] were sequentially introduced into the MXene suspension to synthesize the PBA-loaded MXene composite material (PMX). SEM and TEM characterization confirmed the uniform and stable dispersion of Cu-PBA nanoparticles on the MXene nanosheets ( Figure 2 (c, f)). SEM-EDX analysis (Fig. 2(g)) verifies the uniform distribution of C, Fe, N, Cu, K, and Ti, further confirming the successful integration of Cu-PBA nanoparticles onto MXene nanosheets.

[0041] X-ray diffraction (XRD) analysis of the crystal phase structures of Cu-PBA, MXene, and PMX Figure 3 (a) It is found that after etching, the intensity of the characteristic diffraction peak of the Ti3AlC2 MAX material is significantly reduced, and an obvious diffraction peak appears at 7.2°, corresponding to the (002) crystal plane of MXene. In addition, the XRD spectrum of PMX shows characteristic peaks consistent with the standard diffraction peaks of Cu-PBA (PDF #00-002-0383) (such as 17.76° (200), 25.20° (220), 36.04° (400)), indicating that Cu-PBA is successfully loaded on MXene.

[0042] Analysis by Fourier transform infrared spectroscopy (FT-IR) Figure 3 (b) Both Cu-PBA and PMX show the characteristic peaks of -C≡N, among which the characteristic peak of Cu-PBA (2170 cm -1and 2100 cm -1 ) shifted to 2060 cm in PMX -1 , further indicating that there is an interaction between Cu-PBA and MXene.

[0043] In addition, X-ray photoelectron spectroscopy (XPS) analysis showed that the chemical states of elements in Cu-PBA and MXene, including C, Fe, N, Cu, K, Ti, and O ( Figure 3 (c)). Among them, the C 1s spectrum of PMX is decomposed into three characteristic peaks: 288.48 eV (C=O), 286.24 eV (C≡N) and 284.8 eV (CC) ( Figure 3 (d)), further confirming that Cu-PBA is bound to the MXene surface via chemical interactions.

[0044] ICP-OES test analyzes the atomic ratio, and the mass fraction of each metal is as follows:

[0045]

[0046] Embodiment 2 Referring to the method of Example 1, the amount of copper nitrate was changed to 0.5 mmol, 1 mmol, 2 mmol, 4 mmol, 8 mmol, and 10 mmol, respectively, and the molar ratio of K3[Fe(CN)6] to copper nitrate was 1:1. The materials obtained were called PMX-1, PMX-2, PMX-3, PMX-4, PMX-5, and PMX-6, respectively. Comparative Example 1

[0047] In the absence of MXene nanosheets, Cu-PBA was prepared according to the method of Example 1 for comparison. Example 3 Study on the performance of PMX adsorbing cesium ions

[0048] Kinetic experiment process: 10 mg of PMX material was added into 10 mL of 100 ppm Cs + The samples were taken at different times under continuous stirring in a transparent sample bottle and detected by ICP-MS.

[0049] Isotherm experiment process: 10 mg PMX material was added into 10 mL of Cs + The samples were placed in transparent sample bottles and placed in water baths at 298.15K, 308.15K, and 318.15K, respectively. After stirring for 12 h, samples were taken and detected by ICP-MS.

[0050] By using 100 mg / L Cs +The adsorption kinetics of Cu-PBA, MXene and PMX were tested in the solutions. The results showed that the adsorption process of PMX can be divided into two stages: the first stage occurs within the first 2 minutes, when the adsorption rate increases rapidly; the second stage, the adsorption rate gradually slows down and reaches adsorption equilibrium within 5 minutes ( Figure 4 ). This shows that PMX has very fast adsorption performance, which is significantly improved compared with single Cu-PBA and MXene materials.

[0051] In order to further study the adsorption process, pseudo-first-order and pseudo-second-order kinetic models were used to fit the experimental data. The results showed that the goodness of fit of the pseudo-second-order kinetic model (R 2 >0.99) was significantly better than the pseudo-first-order kinetic model, indicating that the adsorption of Cs⁺ by PMX was mainly a chemical adsorption process (Table 1).

[0052] Table 1 Constants and correlation coefficients related to the kinetic model

[0053] like Figure 5 The results show that the initial concentration of Cs in the range of 0.1 to 1500 ppm was used at pH = 1. + The solution was tested for adsorption isotherms at different temperatures. The experimental data fit well with the Langmuir-Freundlich model, indicating that there are different energy sites on the adsorbent surface and there is a superposition of different adsorption mechanisms. The maximum theoretical adsorption capacity (q max ) was 408.2 mg / g (Table 2), which was significantly higher than many traditional adsorbent materials.

[0054] Table 2 Adsorption parameters of Langmuir, Freundlich and Langmuir-Freundlich models

[0055] Example 4 Adsorption selectivity and water environment influence PMX exhibits good selectivity and good adsorption performance in different water environments.

[0056] Different salts (metal chlorides or nitrates, such as CsCl) were dissolved in HNO3 (different concentrations) to prepare mixed ion solutions with each metal ion concentration of 100 ppm; 10 mg of PMX material was added to a transparent sample bottle containing 10 mL of the mixed solution, and the sample was taken after stirring for 12 hours. The taken solution was filtered through a 0.22 μm filter head, diluted in 0.1 M hydrochloric acid, and detected by ICP-MS.

[0057] The adsorption amount (qt) and adsorption efficiency (R) were calculated using the following formulas.

[0058] (1) (2) Where C0, C t is the Cs in the solution after adsorption time t + is the initial and final concentration; V (L) is the volume of the aqueous phase; m (g) is the amount of adsorbent.

[0059] Pseudo first-order kinetic equation (Equation 3) and pseudo second-order kinetic equation (Equation 4).

[0060] (3) (4) where q e (mg / g) and q t (mg / g) represent the amount of adsorbent absorbed per unit mass of adsorbent at equilibrium and time t respectively; K1 (S –1 ), K2 (g mg –1 S –1 ) represent the adsorption rate constants of pseudo-first-order kinetics and pseudo-second-order kinetics, respectively.

[0061] By changing Cs + The initial concentration of the material was measured at 298.15 K to measure the Cs + The data obtained were processed by the following formula.

[0062] Langmuir model: (5) Freundlich model: (6) Langmuir-Freundlich model: (7) where q max (mg / g) is the Langmuir maximum adsorption capacity; K L is the Langmuir adsorption isotherm constant related to the interaction energy or net enthalpy of adsorption, representing the affinity between the adsorbate and the adsorbent; K F and n is the Freundlich constant, which indicates the relative adsorption capacity and adsorption intensity of the adsorbent; K L-Fand n is the Langmuir-Freundlich constant, which indicates the relative adsorption capacity and adsorption intensity of the adsorbent.

[0063] where q e and q t (mg / g) is the adsorption capacity at equilibrium and time t; k1 (min -1 ) and k2 (min -1 ) represent pseudo first-order and pseudo second-order constants.

[0064] Prepare HNO3 solutions containing different metal ions to explore Cs + Selective adsorption on PMX. Figure 6(a) shows the adsorption behavior of PMX for a series of metal ions (e.g. M 4+ : Zr 4+ ; M 3+ : Sb 3+ , Tm 3+ , Bi 3+ , Fe 3+ , In 3+ , Ce 3+ , Ru 3+ , Al 3+ , and Cr 3 + ; M 2+ : Ni 2+ , Pb 2+ , Cu 2+ , Co 2+ , Ba 2+ , Zn 2+ , Cd 2+ , Mn 2+ , Mg 2+ , Ca 2+ , Sr. 2+ ; M + : Li + ,Cs + , Na + ). As can be seen from the figure, PMX has a strong effect on Cs + The adsorption efficiency of PMX on Cs + The adsorption effect of ions is obviously better than that of other ions.

[0065] Rapid, efficient and selective removal of Cs from seawater and acidic nuclear wastewater +To evaluate the feasibility of PMX in practical applications, its performance in seawater (Cs + concentration 100ppm) and containing 100 ppmCs + Adsorption performance in acidic solution. The results show that PMX can effectively remove Cs in a complex environment with high ionic strength, strong acidity and high concentration of competing ions. + ( Figure 6 (b)). The specific removal rates are: 95.4% for seawater, 95.6% for pH=1 solution, 97.4% for 0.5 M HNO3 solution, and 95.2% for 1 M HNO3 solution; the PMX input is 10 mg, the solution dosage is 10 mL, and the adsorbent dosage m (g): solution volume v (L) = 1:1. These results show that PMX has significant application potential in treating complex wastewater in natural environments.

[0066] Example 5 Desorption and Cycle Performance Desorption and circulation experimental process: 200 mg PMX was placed in 200 mL of 25 ppm Cs at pH = 1. + The adsorbed PMX material was collected by centrifugation, dried, and placed in a saturated KCl solution. After stirring for 12 hours, the solid material was collected by centrifugation, dried, and then placed in a 25 ppm Cs + The process was repeated for five times, and a certain amount of adsorbed Cs was taken each time. + The solution was filtered through a 0.22 μm filter head and diluted in 0.1 M hydrochloric acid to meet the ICP-MS detection requirements.

[0067] In order to evaluate the regeneration ability of PMX, a desorption experiment was carried out on the saturated PMX-Cs using a saturated KCl solution, and its performance in multiple cycles was tested. The experimental results showed that after five consecutive adsorption-desorption cycles, the desorption efficiency only decreased slightly, but still remained above 90% ( Figure 7 ). This result shows that PMX can effectively release Cs during the desorption process. + , and reused for adsorption after simple washing and regeneration, while its structure and function remain basically stable. This excellent regenerativeness and cyclic stability make PMX an economical, efficient and suitable adsorption material for long-term use, especially in actual wastewater treatment.

[0068] Example 6 PMX with different Cu-PBA loadings 10 mg of PMX material was added into 10 mL of 100 ppm Cs + in a transparent sample bottle (100ppm Cs +Standard solution, medium is 5% nitric acid solution), stirred for 5 hours, then sampled and detected by ICP-MS. + The adsorption effect of Figure 8 . Embodiment 7

[0069] Referring to the preparation method of Cu-PBA in Example 1, copper nitrate was replaced by nickel nitrate and iron nitrate to prepare Ni-PBA and Fe-PBA respectively; the feed ratio during adsorption was m:v=1:1, the adsorption time was 6h, and the adsorption solution was 100ppm Cs + The solution was prepared with 5% nitric acid as the medium and detected by ICP-MS. + The adsorption effect of Fig. 9 .

[0070] MXene is an emerging two-dimensional material that shows great potential in environmental remediation due to its high chemical stability, rich negatively charged functional groups and large specific surface area. However, MXene materials are easily oxidized to TiO2 in aqueous environments, and this chemical instability limits their wide application. Therefore, how to utilize the unique properties of MXene while enhancing its chemical stability has become the key to research. The present invention combines MXene with Cu to introduce 2+ and K3[Fe(CN)6] to form a 3D composite material PMX. Potassium copper ferrocyanide (Cu-PBA) nanoparticles were uniformly loaded on the MXene surface by in-situ growth technology to prepare a stable MXene-based composite material (PMX). The material exhibits excellent cesium ion adsorption performance in acidic environment and seawater, with an adsorption equilibrium time as short as 5 minutes and an adsorption capacity as high as 408.2 mg / g, which is significantly better than traditional adsorbents. The present invention provides an efficient, low-cost and easy-to-recycle solution for radioactive wastewater treatment and rare resource recovery.

Claims

1. A metal-modified MXene nanosheet three-dimensional composite material, comprising a MXene nanosheet and a metal composite on its surface, characterized in that: The metal complex includes K2Cu3(Fe(CN)6)2.

2. The method for preparing the metal-modified MXene nanosheet three-dimensional composite material according to claim 1 comprises the following steps: reacting copper salt and K3[Fe(CN)6] on MXene nanosheets to prepare the metal-modified MXene nanosheet three-dimensional composite material.

3. The method for preparing the metal-modified MXene nanosheet three-dimensional composite material according to claim 2 comprises the following steps: mixing copper salt and MXene nanosheets, and then mixing with K3[Fe(CN)6] to prepare the metal-modified MXene nanosheet three-dimensional composite material.

4. The method for preparing the metal-modified MXene nanosheet three-dimensional composite material according to claim 3 comprises the following steps: mixing copper salt and MXene nanosheets in a solution, and then mixing with K3[Fe(CN)6] to prepare the metal-modified MXene nanosheet three-dimensional composite material.

5. A three-dimensional adsorbent, the active ingredient of which comprises the metal-modified MXene nanosheet three-dimensional composite material according to claim 1.

6. Use of the metal-modified MXene nanosheet three-dimensional composite material according to claim 1 or the three-dimensional adsorbent according to claim 5 as or in the preparation of an adsorption material.

7. Use of the metal-modified MXene nanosheet three-dimensional composite material according to claim 1 or the three-dimensional adsorbent according to claim 5 as or in the preparation of a metal adsorption material.

8. Use of the metal-modified MXene nanosheet three-dimensional composite material according to claim 1 or the three-dimensional adsorbent according to claim 5 as or in the preparation of a radioactive metal adsorption material.

9. The use according to claim 8, characterized in that: Radioactive metals include cesium.

10. A method for adsorbing metals, comprising the following steps: mixing the metal-modified MXene nanosheet three-dimensional composite material according to claim 1 or the three-dimensional adsorbent according to claim 5 with a system containing metal to complete the adsorption of the metal.

Citation Information

Patent Citations

  • Adsorbent for removing cesium ions in water and application of adsorbent in Cs absorption

    CN108212072A

  • Preparation method of magnetic nano composite material

    CN110193345A

  • MXene composite material as well as preparation method and application thereof

    CN116139823A

  • Modified MXene adsorption material as well as preparation method and application thereof

    CN116586029A